Cancer Grand Challenges—a call to reunify the physical and life sciences communities. (7th January 2016) - Scott, David; Weston, Kathleen
Abstract: In order to speed progress in cancer research, it is necessary to recruit the best scientists, irrespective of discipline or geographical location, to tackle the barriers that still lie ahead. Cancer Research UK's recently launched £100m Grand Challenge grants scheme is specifically designed to facilitate collaboration between the physical and biological sciences. We are seeking multidisciplinary, international teams of scientists to come up with innovative, ambitious proposals to solve seven of the toughest challenges left in cancer research. The scheme is intended to catalyse the formation of a global Grand Challenge community, and to reward hypothesis-driven, blue-skies thinking.